If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5 + 6k) + 16 = -90 (5 * -2 + 6k * -2) + 16 = -90 (-10 + -12k) + 16 = -90 Reorder the terms: -10 + 16 + -12k = -90 Combine like terms: -10 + 16 = 6 6 + -12k = -90 Solving 6 + -12k = -90 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -12k = -90 + -6 Combine like terms: 6 + -6 = 0 0 + -12k = -90 + -6 -12k = -90 + -6 Combine like terms: -90 + -6 = -96 -12k = -96 Divide each side by '-12'. k = 8 Simplifying k = 8
| A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 | | 1300.46=2*3.14r^2+2*3.14*6.2 | | y=100+x+(7-x) | | y(15x-18)= | | 4x+7+3x-17=180 | | X=-16x^2+38 | | 2x-x^2=.91 | | 3b^2-4b-4= | | z^2+11z=-24 | | -5+2(1)=-4 | | x-.3x=30.80 | | 2+Y+2=10-3 | | 5x-5+x-7=180 | | (3y+5)(6y-1)= | | 4+Y=18-Y |